Analisis SWOT Terhadap Strategi Pengembangan Usaha Warung Nasi Priangan di Tasikmalaya - Mamik M. Fuadi; Ernawati Ernawati; Dina Rizki (Cipasung Techno Pesantren: Jurnal Ilmiah, 2023)
Warung Nasi Priangan is a business engaged in the culinary field which was founded in 2001. According to sales turnover data for the past 1 year, Warung Nasi Priangan has experienced a decline in turnover from time to time so that revenue does not meet the desired target. The research method used to collect the required data is a descriptive qualitative method. From the data obtained, an analysis was carried out using the SWOT analysis method with the aim of developing a business development strategy for Warung Nasi Priangan to increase sales turnover. The results of the SWOT analysis show that the right strategy to be used by Warung Nasi Priangan is the SO Strategy, namely by maintaining good taste, good service and adequate facilities to keep customers loyal, as well as expanding marketing to increase turnover by maintaining good relations between employees and consumer. However, the results of the SWOT analysis are irrelevant to the actual situation.